The accuracy of pharmacokinetic parameter measurement in DCE-MRI of the breast at 3 T - Di Giovanni, P.; Azlan, C.A.; Ahearn, T.S.; Semple, S.I.; Gilbert, F.J.; Redpath, T.W. (IOP Publishing, 2010)
The purpose of this work is to quantify the accuracy of pharmacokinetic parameter measurement in DCE-MRI of breast cancer at 3 T in relation to three sources of error. Individually, T1 measurement error, temporal resolution and transmitted RF field inhomogeneity are considered. Dynamic contrast enhancement curves were simulated using standard acquisition parameters of a DCE-MRI protocol. Errors on pre-contrast T1 due to incorrect RF spoiling were considered. Flip angle errors were measured and introduced into the fitting routine, and temporal resolution was also varied. The error in fitted pharmacokinetic parameters, K(trans) and v(e), was calculated. Flip angles were found to be reduced by up to 55% of the expected value. The resultant errors in our range of K(trans) and v(e) were found to be up to 66% and 74%, respectively. Incorrect T1 estimation results in K(trans) and v(e) errors up to 531% and 233%, respectively. When the temporal resolution is reduced from 10 to 70 s K(trans) drops by up to 48%, while v(e) shows negligible variation. In combination, uncertainties in tissue T1 map and applied flip angle were shown to contribute to errors of up to 88% in K(trans) and 73% in v(e). These results demonstrate the importance of high temporal resolution, accurate T1 measurement and good B1 homogeneity.